Solve: $$\int_0^\frac{\pi}{2}\frac{\sqrt{\sin{x}\cos{x}}}{\cos{x}+1}dx$$

I tried

$$\int_0^\frac{\pi}{2}\frac{\sqrt{\sin{x}\cos{x}}}{\cos{x}+1}dx=\sum_{k=0}^\infty(-1)^k\int_0^\frac{\pi}{2}(\sin{x})^\frac{1}{2}(\cos{x})^{k+\frac{1}{2}}=\sum_{k=0}^\infty(-1)^kB\left(\frac{3}{4},\frac{k}{2}+\frac{3}{4}\right)$$ but it did not work, did it?

  • $\begingroup$ Wolfram says the answer is $\pi\left(\frac{\sqrt{2}}2-\frac{4\sqrt{\pi}}{\Gamma^2\left(\frac14\right)}\right)$ $\endgroup$ – Peter Foreman Apr 10 at 20:06
  • $\begingroup$ Can you post a solution, please? I would help me a lot $\endgroup$ – Reynan Henry Apr 11 at 17:21

We are given:

$$ \int_0^{\pi/2} \frac{\sqrt{\sin x\cos x}\,dx}{1+\cos x} $$

Put $t=\tan\tfrac{x}{2}$; then

$$ \sin x = \frac{2t}{1+t^2} \quad\quad \cos x = \frac{1-t^2}{1+t^2} \quad\quad dx = \frac{2\,dt}{1+t^2} $$


$$ \sqrt{\sin x\cos x} = \frac{2t(1-t^2)}{1+t^2} $$


\begin{align} 1 + \cos x &= 1 + \frac{1-t^2}{1+t^2} \\ &= \frac{1+t^2+1-t^2}{1+t^2} = \frac{2}{1+t^2} \end{align}

so that

$$ \int_0^{\pi/2}\frac{\sqrt{\sin x\cos x}\,dx}{1+\cos x} = \int_0^1\frac{\sqrt{2t(1-t^2)}\,dt}{1+t^2} $$

This is an elliptic integral. Here's my attempt at expressing it in terms of the Legendre canonical forms: put $t^2=v$; then $dt=2v\,dv$ and the integral becomes

\begin{align} \int_0^1 \frac{\sqrt{2t(1-t^2)}\,dt}{1+t^2} &= \int_0^1 \frac{\sqrt{2v^2(1-v^4)}(2v\,dv)}{1+v^4} \\ &= 2\sqrt2 \int_0^1 \frac{v^2(1-v^4)}{1+v^4}\frac{dv}{\sqrt{1-v^4}} \\ &= 2\sqrt2 \int_0^1 \left(\frac{i}{1+iv^2}-\frac{i}{1-iv^2}-v^2\right)\frac{dv}{\sqrt{1-v^4}} \\ &= 2\sqrt2(i\Pi(-i,i)-i\Pi(i,i)-E(i)+K(i)) \end{align}

where $K,E,\Pi$ are the first, second and third complete elliptic integrals, in terms of the modulus $k$.

Wolfram Alpha gives an exact value

$$ 2\sqrt 2(K(i)-E(i)) = -\frac{4\pi^{3/2}}{\Gamma(\tfrac{1}{4})^2} $$

which, given Peter Foreman's comment, looks right. But W|A does not give an exact value for the term involving the $\Pi$'s, so I think I made a mistake there. I'll look into that later. I'll also try and see if I can prove these values for the integrals.

Update: In

$$ E(i) - K(i) = \int_0^1\frac{v^2\,dv}{\sqrt{1-v^4}} $$

put $r=v^4$; then $dv=v^{-3}\,dr/4$ and the integral becomes

\begin{align} \int_0^1 \frac{v^2\,dv}{\sqrt{1-v^4}} &= \frac{1}{4}\int_0^1 (1-r)^{-1/2}r^{1/2}r^{-3/4}\,dr \\ &= \frac{1}{4}{\rm B}(\tfrac{1}{2},\tfrac{3}{4}) = \frac{1}{4}\frac{\Gamma(\tfrac{1}{2})\Gamma(\tfrac{3}{4})}{\Gamma(\tfrac{5}{4})} \\ &= \frac{\Gamma(\tfrac{1}{2})\Gamma(\tfrac{3}{4})}{\Gamma(\tfrac{1}{4})} \end{align}

By the reflection formula,

$$ \Gamma(\tfrac{1}{4})\Gamma(\tfrac{3}{4}) = \frac{\pi}{\sin\tfrac{\pi}{4}} = \pi\sqrt 2 $$

Using next $\Gamma(\tfrac{1}{2})=\sqrt\pi$ we put everything together yielding

$$ E(i) - K(i) = \frac{\pi^{3/2}\sqrt2}{\Gamma(\tfrac{1}{4})^2} $$

I'll look into the case of the $\Pi$'s next.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.